The Matthew effect in talent management strategy: reducing exhaustion, increasing satisfaction, and inspiring commission among boundary spanning employees. Issue 3 (10th June 2021) - Srivastava, Rajesh V.; Tang, Thomas
Abstract : Purpose: In an ongoing War for Talent, what are the intangible and tangible return on investments (ROIs) for boundary-spanning employees? This study aims to develop a formative structural equation model (SEM) of the Matthew effect in talent. management. Design/methodology/approach: This study develops a formative SEM theoretical model. Training and development (T&D) are the two antecedents of the latent construct – talent management strategy (TMS). This study frames the latent construct (TMS) in the proximal context of reducing burnout (cynicism and inefficacy), the distal context of subjective and intangible outcomes (job and life satisfaction) and the omnibus context of objective, tangible and financial rewards (the sales commission). The study collected data from multiple sources – objective sales commission from personnel records and subjective survey data from 512 sales employees. Findings: The empirical discoveries support the theory. Both T&D contribute significantly to the TMS, which reduces burnout in the immediate context. TMS enhances job satisfaction more than life satisfaction in the distal context. TMS significantly and indirectly improves boundary spanners' sales commission in the omnibus context via life satisfaction, but not job satisfaction. The model prevails for the whole sample, men, but not women. Practical implications: Our discoveries offer practical implications for the Matthew effect in talent management: policymakers must cultivate T&D, develop TMS, facilitate the spillover effect from job satisfaction to life satisfaction, concentrate on the meaning in their lives and take their mind off money. TMS ultimately helps ignite these boundary spanners' sales commission and their organization's bottom line and financial health. The rich get richer. Originality/value: It is life satisfaction (not job satisfaction) that excites boundary-spanning employees' high level of sales commission. Our model prevails for the whole sample and men, but not for women. Job satisfaction spills over to life satisfaction for the entire sample, for men, but not for women. The results reveal gender differences.